Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/tbed.13855
|View full text |Cite
|
Sign up to set email alerts
|

First digital characterization of the transhumance corridors through Benin used by cattle herds from Burkina Faso and associated risk scoring regarding the invasion of Rhipicephalus ( Boophilus ) microplus

Abstract: Article type : Original Article First digital characterization of the transhumance corridors through Benin used by cattle herds from Burkina Faso and associated risk scoring regarding the invasion of Rhipicephalus (Boophilus) microplus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Babesia bovis was evidenced in cattle in eastern BF, however its principal vector R. microplus (Dantas-Torres et al, 2012;Grisi et al, 2014), was not found there. This suggests cattle of eastern BF were infected with B. bovis after their exposure to R. microplus or other competent species, during their seasonal migration in northern BN through transhumance corridors (Zannou et al, 2020). However, this hypothesis requires more investigations considering cattle transboundary movements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Babesia bovis was evidenced in cattle in eastern BF, however its principal vector R. microplus (Dantas-Torres et al, 2012;Grisi et al, 2014), was not found there. This suggests cattle of eastern BF were infected with B. bovis after their exposure to R. microplus or other competent species, during their seasonal migration in northern BN through transhumance corridors (Zannou et al, 2020). However, this hypothesis requires more investigations considering cattle transboundary movements.…”
Section: Discussionmentioning
confidence: 99%
“…BN and BF are two countries sharing a border of 285 kms through which seasonal migrations of cattle occur in order to find pasture and watering places during the dry season. Such migrations favor the contact between herds mainly at grazing and watering places, raising the potential spread of transboundary diseases (Zannou et al, 2020). This transversal survey aims to assess the current situation of tick species and the associated pathogens in specific geographical locations corresponding to the departure (eastern BF) and arrival zones (northern BN) of the seasonal migration between the two countries.…”
Section: Introductionmentioning
confidence: 99%
“…This animal belongs to another herd which has also stayed in the same commune in Benin. According to the distribution of risk scores for the occurrence and establishment of R. microplus in the study area (Zannou et al, 2020), this commune appears to be one of the localities showing the highest risk scores (69-80%). As some transhumant herds stayed in the same commune, this could lead to suggest an infestation of more transhumant cattle by R. microplus, but which were not detected.…”
Section: Discussionmentioning
confidence: 98%
“…In the north of this country, the Atacora and Alibori departments receive a rainfall ranging from 700 to 1200 mm/year, which makes this region a suitable area for livestock farming and a favourite destination for Niger, Nigeria, Mali and Burkina Faso (BF) herders, seeking pasture and water points during the dry season (Lesse et al, 2015;Bouslikhane, 2015). After having walked between 150 and 200 km, farmers of eastern BF, coming from Gourma, Kompienga and Tapoa provinces, reach northern BN (Atacora and Alibori departments) through four transhumance corridors, and three entry points identified by Zannou et al (2020) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation